2022
DOI: 10.1080/17461391.2022.2065927
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise is tied to emotion‐related impulsivity: insights from correlational analyses in healthy humans

Abstract: Seminal work has found a negative association between physical exercise and impulsivity levels in humans. This paper aims to strengthen these findings by evaluating the association between the amount of self-reported physical exercise per week and emotion-related impulsivity whilst considering age and gender as covariates on a large-scale dataset.Participants completed an online self-report questionnaire about emotion-related impulsivity (i.e. Feelings Trigger Action) and exercise-related questions. After qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In previous studies, Javalle and Cheng used the exercise scale measure to measure the physical activity participation of different age groups and the status of physical exercise levels. They verified the scale's reliability, and its reliability level is high (0.70-0.80) (47).…”
Section: Physical Activity Rating Scale (Pars-3)mentioning
confidence: 84%
“…In previous studies, Javalle and Cheng used the exercise scale measure to measure the physical activity participation of different age groups and the status of physical exercise levels. They verified the scale's reliability, and its reliability level is high (0.70-0.80) (47).…”
Section: Physical Activity Rating Scale (Pars-3)mentioning
confidence: 84%
“…Previous work has shown that increased impulsivity is tied to lower physical activity levels (Javelle, Vogel, et al, 2022; Javelle et al, 2020). Here, we extend this work by showing that ERI and non‐ERI were tied to less physical activity (indexed by low GPAQ) when controlling for poor sleep quality (indexed by high PSQI).…”
Section: Discussionmentioning
confidence: 97%
“…Intriguingly, regular physical activity may also have links with impulsivity and many of these related biomarkers. For example, less self‐reported engagement in physical activity was correlated with ERI and non‐ERI (Gunten et al, 2020; Javelle, Vogel, et al, 2022; Javelle et al, 2020). In one randomized controlled trial, participants who took part in 8 weeks of physical exercise intervention demonstrated postintervention reductions in ERI and non‐ERI (Javelle et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation